2014
DOI: 10.1007/jhep05(2014)083
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical constraints on additional Higgs bosons in light of the 126 GeV Higgs

Abstract: We present a sum rule for Higgs fields in general representations under SU (2) L × U (1) Y that follows from the connection between the Higgs couplings and the mechanism that gives the electroweak bosons their masses, and at the same time restricts these couplings. Sum rules that follow from perturbative unitarity will require us to include singly and doubly charged Higgses in our analysis. We examine the consequences of these sum rules for Higgs phenomenology in both model independent and model specific ways.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(91 reference statements)
0
32
0
Order By: Relevance
“…The authors of [1,4] examined the production and decays of the observed Higgs for the septet, while [5] explored how the electroweak quantum numbers of an additional scalar field, such as the septet, could be determined through a measurement of the Higgs-Higgs-vector-vector coupling. The sum rules for general scalar representations of SU(2) L × U(1) Y were studied in [6] using perturbative unitarity, including the septet model as a specific example.…”
Section: Jhep05(2014)150mentioning
confidence: 99%
“…The authors of [1,4] examined the production and decays of the observed Higgs for the septet, while [5] explored how the electroweak quantum numbers of an additional scalar field, such as the septet, could be determined through a measurement of the Higgs-Higgs-vector-vector coupling. The sum rules for general scalar representations of SU(2) L × U(1) Y were studied in [6] using perturbative unitarity, including the septet model as a specific example.…”
Section: Jhep05(2014)150mentioning
confidence: 99%
“…• Perturbative unitarity [15,[32][33][34][35][36] The two-to-two scattering matrix for this model in the neutral, color singlet channel is 18 × 18 and in Ref. [18] we diagonalize it numerically and illustrate the resulting constraints.…”
mentioning
confidence: 99%
“…This limit is particularly strong for a Z 2 symmetric model [33,39,40]. The dominant one-loop corrections to the perturbative unitarity constraints for the model with softly broken Z 2 symmetry are also available [41].…”
Section: Theoretical Constraintsmentioning
confidence: 99%